Environment, Mix Energies, ASEAN Economies and Education - Sutiah, Sutiah; Supriyono, Supriyono (International Journal of Energy Economics and Policy, 2020)
Education, environment, energies and economic, have several number high impacts of research in 5 years. Data from Dimensions.ai, the most comprehensive research grants database which links grants to millions of resulting publications, clinical trials and patents, have several results about education, environment, energies and economic research, in Studies in Human Society 146 papers, Economics 96 papers, Applied Economics 95 papers, Engineering 93 papers, Policy and Administration 63 papers. Using vosviewer.com analysis, files downloaded from the free version of Dimensions may contain data for at most 2500 documents. (Larger numbers of documents are supported when a subscription-based version of Dimensions is used), we can see that Education have high impact on energy, environment, sustainability and sustainable development. The study aims to investigate the environmental effects of mix energies on the three most polluted countries of ASEAN economies. The study uses the data of the Philippines, Vietnam, and Thailand over the period of 1995-2017 as gathered from the World Bank and Global Economy. The study uses Brush Pagon LM and Pearson CD to test the cross-section dependence among variables while Levin, Lin & Chu (2002) panel unit root test to check the stationary in the data. Westerlund (2007) cointegration and FMOLS tests are applied to analyze the long-run relationship. The result confirms the adverse environmental effects of fossil fuel electricity generation (FEG) and positive environmental effects of solar electricity generation (SEG), nuclear-power electricity generation (NEG), and geothermal electricity generation (GEG) on the ASEAN economies. Wind electricity generation (WEG) and hydroelectricity generation (HEG) do not significantly contribute to deteriorating the environment. The study suggests using GEG, WEG and SEG methods of producing electricity instead of FEG. Keywords: Mix energies, Solar Electricity, Fossil Fuel, Wind Electricity, Hydro Electricity, Nuclear-Power Electricity, Geo-Thermal Electricity. JEL Classifications: O13, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.10400